Exploring the effects of Rumex hanus diets on the flavor and texture of roasted chicken: Insights from metabolomics and sensory analytical approaches - Yuwei Guo; Yaling Gu; Muhammad Aaqil; Zhen Zhang; Feng Zhang; Jingchuan Zheng; Yewei Huang; Ya Wang; Cunchao Zhao (Poultry Science)
This study investigates the effect of dietary incorporation of fermented (FRH) and unfermented Rumex Hanus (URH) on the flavor and texture of roasted chicken. Results demonstrated that, compared to the control group (CON), the FRH group exhibited significantly increased a* and b* values, enhancing the color of the roasted chicken. The FRH group demonstrated a 16.67 % reduction in hardness, a 9.49 % increase in springiness, and a 34.70 % increase in immobilized water as measured by texture profile analysis (TPA) and low-field nuclear magnetic resonance (LF-NMR), confirming a significant increase in tenderness. Scanning electron microscopy (SEM) revealed significantly noticeable fractures and reduced myofiber gaps in the FRH group, further supporting improved tenderness and elasticity. Volatile organic compounds (VOCs) were notably higher in both the URH (34.28 %) and FRH (35.02 %) groups, with a significant increase in alcohols and aldehydes. GC-MS analysis identified that the URH group had the highest content of heterocyclic compounds (37.41 %), including six furan compounds, contributing to a more intense roasted aroma. LC-MS screened 275 non-volatile differential metabolites, including o-tyrosine, l-glutamic acid, and 3,4-dihydro-2H-1-benzopyran-2-one, providing enhanced umami and grassy flavors to the URH samples. The addition of FRH gave the rotisserie chicken the highest sensory score of 76.50. Molecular docking results revealed that amino acid residues such as Ala, Val, and Tyr played a significant role in the stable binding of these compounds. This study provides essential insights into the high-value utilization of fermented and unfermented rumex hanus in poultry diets, offering a valuable reference for improving meat quality and advancing feed formulations in poultry management practices.